Konsepsi Muhammad Rasyid Ridha tentang Syura sebagai Azas Pemerintahan Islam - Yamin, Ahmad (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
In the discourse of Islamic political thoughts, both of pre and modern era, the term "syura" (deliberation) is one of the great issues in the Muslim scholars especially for Islamic political thinkers. One of the great Muslim thinkers in this modern era who countributes significantly in this field is Sayyid Muhammad Rasyid Ridha. His political thoughts are available in his Magna Opus "Khilafat aw al-Imamat al-Uzma". His Ideas are considered brilliant and still in line with the contemporary political discourse. Ridha is in the opinion that the "syura" shoul become the foundations in the "Islamic governement syistem".